Occupational safety and health practice: a study at universities’ laboratories - Victor Subinon, Olivia Calesta; Rosman, Nurul Farah Izzati; Mohd Joharudin, Nurul Farahin; Khalid, Amir; Jaat, Norrizam; Sapit, Azwan; Noranai, Zamri (Penerbit UTHM, 2020)
The Occupational Safety and Health (OSH)’s field has become a topic for the last 30 years. The establishment of the Occupational Safety and Health Administration (OSHA) reflected the recognition that safety in the workplace is a basic expectation for all work staffs. This study describes the needs of universities in relation to planning the provision of occupational health services, by detailing their occupational hazards and risks and other relevant factors in its laboratories. The purpose of this study is to focus on the hazards, OSH practices and injury management in the laboratories in University Tun Hussein Onn Malaysia (UTHM) in Educational Hub Pagoh (Edu Hub Pagoh). This paper is the initial studies to identify the main causes and steps to overcome the hazards that occurred. The purpose was achieved by visiting the university’s laboratories in order to get the real picture of the hazards in that place. The data collection was carried out through site investigation using Hazard Identification, Risk Assessment and Risk Control (HIRARC) and interview with the staffs and students in the university. This study analysed the HIRARC, and suggest recommendations for improving OSH act in the university’s laboratories. These approaches showed that the university sector is large, with a notably wide range of occupational hazards, and other significant factors which must be considered in planning occupational health provision for individual universities or for the sector as a whole.